Complement regulates TLR4-mediated inflammatory responses during intestinal ischemia reperfusion - Pope, Michael R.; Hoffman, Sara M.; Tomlinson, Stephen; Fleming, Sherry D. (My University, 2013)
Innate immune responses including TLR4 and complement activation are required for mesenteric ischemia/reperfusion (IR)-induced tissue damage. We examined the regulation of TLR4 and complement activation in a mouse model of intestinal IR. Intestinal IR induced C3 deposition in a TLR4 dependent manner. In addition, in wild-type but not TLR4 deficient mice, IR significantly increased C3 and Factor B (FB) mRNA expression within the intestine. To further examine the role of TLR4 and complement, we administered the complement inhibitor, CR2-Crry, to target local complement activation in wild-type C57Bl/10, and TLR4 deficient B10/ScN mice. TLR4 deficient mice sustained less damage and inflammation after IR than wild-type mice, but administration of CR2-Crry did not further reduce tissue damage. In contrast, CR2-Crry treatment of wild-type mice was accompanied by a reduction in complement activation and in C3 and FB transcription in response to IR. CR2-Crry also significantly decreased intestinal IL-6 and IL-12p40 production in both the wild-type and TLR4 deficient mice. These data indicate that TLR4 regulates extrahepatic complement production while complement regulates TLR4-mediated cytokine production during intestinal IR.
Keywords: TLR4; Rodent; Mucosa; Complement; Inflammation; Mouse